Meeting housing needs of the poor and needy Muslims through zakat and wakaf - Abdul Rashid, Khairuddin; Mohd Fauzi, Puteri Nur Farah Naadia; Hasan, Sharina Farihah (Malaysian Institute of Planners, 2018)
Meeting housing needs of the poor and needy is a continuous challenge. The challenge is exacerbated, among others, by the continuous and upward increases in the cost of living, population growth and the availability of resources especially suitable and affordable lands for development. The Government intervenes through policy implementation and assistance in the forms of subsidies and the provision of social housing. In Islam, there is an opportunity to empower the poor and needy to be assisted i.e. they could receive help in meeting their affordable housing needs through zakat and wakaf. Applying desk study and discussions with experts, this paper initially reviews the housing needs of the poor and needy and the ensuing issues and challenges. This is followed by a review on zakat and wakaf and their involvement in providing housing assistance to the poor and needy Muslims. Thereafter, this paper assesses the potential of zakat and wakaf in the provision of affordable housing and highlights key challenges. The paper concludes with a list of strategies considered worthy for further and detailed consideration. The significance of the study and its findings is viewed in terms of the innovative idea in promoting zakat and wakaf to integrate their resources instead of working in a silo; therefore the synergy resulting therefrom could facilitate uplifting the socio-economic conditions of the poor and needy in the context of meeting their housing needs.